Indicators of impending pig kidney and heart xenograft failure: Relevance to clinical organ xenotransplantation - Review article. (October 2019) - Iwase, Hayato; Jagdale, Abhijit; Yamamoto, Takayuki; Zhang, Guoqiang; Li, Qi; Foote, Jeremy; Ayares, David; Ekser, Burcin; Hara, Hidetaka; Cooper, David K.C.
Abstract: In pig-to-baboon organ xenotransplantation, coagulation dysfunction and inflammation have been suggested to be associated with acute humoral xenograft rejection. We have evaluated platelet counts, plasma fibrinogen, and parameters of inflammation as indicators of xenograft failure in baboons with kidney and heart grafts from genetically-engineered pigs. Blood chemistry, hematologic, immune, and inflammatory parameters were measured in recipient baboons (n = 16) with organs from α1, 3-galactosyltransferase gene-knockout pigs expressing human complement- and coagulation-regulatory proteins. Thrombocytopenia and reduction of plasma fibrinogen level were observed in baboons developing graft failure, and these correlated with histopathologic findings of glomerular and interstitial thrombosis, and vasculitis in the graft. Not infrequently, in baboons with pig kidney grafts, a consumptive coagulopathy developed prior to a rise in serum creatinine. In contrast, when kidney graft survival was prolonged, no changes were observed in platelet count or fibrinogen. Indicators of the inflammatory response, particularly the serum amyloid A (SAA) assay, increased when graft failure was developing. There were no changes in cellular immune parameters, e.g., T or B cell counts or phenotypes that indicated graft failure. Therefore, in clinical xenotransplantation, noninvasive parameters (e.g., platelet count, fibrinogen level, SAA) might provide more reliable indicators of impending xenograft failure than measurements of immune parameters or even of serum creatinine. Highlights: Thrombocytopenia and reduction in fibrinogen when xenograft failure is developing. Increased inflammatory response (e.g., SAA) when xenograft failure is developing. Consumptive coagulopathy occurs prior to a rise in serum creatinine. Correlation of platelet count and fibrinogen with histopathologic findings. Reliable indicators of impending xenograft failure in clinical xenotransplantation.